MODAL SOSIAL PEKERJA MINYAK KAYU PUTIH DI DESA WAPLAU - Hamiru, Hamiru; Umanailo, M. Chairul Basrun; Hehamahua, Hayati; Hamid, Iskandar (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
The social capital found in the community in Waplau Village of Buru Regency grows and develops in line with the achievement of fulfilling the necessities of life. The relationship of cooperation in the distillation of oil from eucalyptus leaves is built among landowners, tenants, renters, and receptors so that social capital is built with participation, trust, cooperation, and reciprocity become the norm which continues to be maintained. This research was conducted based on the preference for the implementation of the eucalyptus oil refining process in Waplau Village as an effort to gain profits and fulfill household needs. The research location was focused in Waplau Village considering the number of eucalyptus oil workers which was more dominant compared to other villages in Buru Regency; the research samples were eucalyptus landowners, land tenants, rental workers, and collectors. The researcher uses primary data obtained from the results of observations and direct interviews with informants. The data analysis method used proposed by Miles and Huberman and Spradley. The results showed that social capital is an indicator of the success of eucalyptus oil workers in achieving goals. The social capital aspect has a strong relationship with the existence of landowners, tenants, and rental workers, as well as working groups among anaconda, leaf sequencer, cook and laborer in completing the task of refining oil so that social capital is able to become an instrument for eucalyptus oil productivity in Waplau village.